1993
DOI: 10.1038/nbt1293-1565
|View full text |Cite
|
Sign up to set email alerts
|

Use of Living Columns to Select Specific Phage Antibodies

Abstract: Here we demonstrate that it is possible to confront two recombinant microorganisms in order to select one using the other. We have shown that an epitope derived from p21ras expressed within the outer membrane protein, LamB, can be recognized both by the monoclonal antibody Y13-259, as well as the single chain Fv fragment derived from it. This specificity, which is maintained when the Y13-259 single chain Fv is expressed as a fusion protein with the phage fd gene 3 protein, has allowed us to use the living colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…We then performed an ELISA (Fig. 6A) which detects the epitope directly on spheroplasts (26,27). This analysis showed that antibody 9E10 reacts very strongly with the tagged whole hup2AR, indicating that the epitope at the N terminus is exposed on the outside ofthe membrane.…”
Section: Resultsmentioning
confidence: 99%
“…We then performed an ELISA (Fig. 6A) which detects the epitope directly on spheroplasts (26,27). This analysis showed that antibody 9E10 reacts very strongly with the tagged whole hup2AR, indicating that the epitope at the N terminus is exposed on the outside ofthe membrane.…”
Section: Resultsmentioning
confidence: 99%
“…25) into pVP16*. pscFvPM163-VP16* and pscFvPM163R4-VP16 were subcloned as NcoI-NotI fragments from pPM163 and pPM163R4 (12) (provided by P. Martineau, Institut Pasteur, Paris) into pCANTAB6 and subcloned again as SfiI-NotI fragments from pCANTAB6scFvPM163 and pCANTAB6scFvPM163R4, respectively, into pVP16*.…”
Section: Methodsmentioning
confidence: 99%
“…The Y13.259-ScFv gene was subcloned from the secretory bacterial expression vector, p3JF4 [8], as a PstI-BamHI fragment and inserted into the leaderless ScFv expression vector, pJM1. This plasmid has been generated by deleting the pelB secretory leader sequence of p3JF4, thus yielding a leaderless 5' of the ScFv gene (corresponding to the amino acid sequence Met Gin Val Gin ).…”
Section: Plasmidsmentioning
confidence: 99%